Prevalence of skeletal malocclusions in the population of the province of Azuay - Ecuador (Research, Society and Development, 2021)
Objective: To establish the prevalence of skeletal malocclusions in the population of the province of Azuay-Ecuador, through cephalometric analysis of lateral radiographs in order to make a comparison with the different regions of Ecuador. Materials and methods: Quantitative, descriptive, retrospective and longitudinal study in which clinical records of men and women between 11 and 50 years old who attended the maxillofacial surgery service of the Monte Sinaí hospital in the city of Cuenca - Ecuador were analyzed, with a diagnosis of skeletal malocclusions. 308 clinical records were obtained from 2010 to 2020, of which 202 were included in this investigation because they had a cephalometric X-ray of the patient, taken in the radiology and imaging service of the Monte Sinaí Hospital. Results: After statistical analysis, we found that 49% of the sample was class III, 43.56%  class II and 7.42% class I. According to the bone base involved, class III can be presented as: maxilla normal with mandibular prognathism (35.64%), maxillary protrusion with mandibular prognathism (22.77%) or maxillary retrusion with mandibular prognathism (13.36%). Conclusion: The most prevalent skeletal malocclusion in this population is class III and the least frequent is class I, being greater in men than in women in an age range of 16 to 20 years.